2017
DOI: 10.1007/jhep03(2017)015
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous electrodynamics of neutral pion matter in strong magnetic fields

Abstract: The ground state of quantum chromodynamics in sufficiently strong external magnetic fields and at moderate baryon chemical potential is a chiral soliton lattice (CSL) of neutral pions [1]. We investigate the interplay between the CSL structure and dynamical electromagnetic fields. Our main result is that in presence of the CSL background, the two physical photon polarizations and the neutral pion mix, giving rise to two gapped excitations and one gapless mode with a nonrelativistic dispersion relation. The nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…One is to analyze physics in the background magnetic field, spatially varying axion field, and so on. It has been shown that in non-trivial backgrounds, mass spectra of the axion and photon are deformed [26,54,55,116]. We may understand such deformations of the phase structure by using higher-form symmetries, 3group, and their 't Hooft anomalies (see e.g., ref.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One is to analyze physics in the background magnetic field, spatially varying axion field, and so on. It has been shown that in non-trivial backgrounds, mass spectra of the axion and photon are deformed [26,54,55,116]. We may understand such deformations of the phase structure by using higher-form symmetries, 3group, and their 't Hooft anomalies (see e.g., ref.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To understand its possible realization in heavy ion collisions more realistically, it is necessary to take into account the finite-temperature effects on the η CSL; see also ref. [46] for the study on the low-temperature effects on the π 0 CSL in a magnetic field. Further studies in this direction will be reported elsewhere.…”
Section: Jhep07(2020)196 4 Discussion and Conclusionmentioning
confidence: 99%
“…It is known that one-dimensional modulations in pion condensates [1] are unstable at finite temperatures (although quasi-long-range order may persist). On the other hand, CSL in QCD seems to be stable under quantum fluctuations [7] and the effects of finite temperature are subject of ongoing work.…”
Section: Discussionmentioning
confidence: 99%